Analisa Kinerja Ruas Jalan Panglima Sudirman Singosari-Malang - Andi Syaiful Amal; Azhar Adi Darmawan; Amalia Nur Adibah; Chairil Saleh (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Highways are transportation infrastructure that is very important in supporting land transportation. Without being matched by an increase in road infrastructure, it will result in an excessive load on the road structure and will cause congestion. Congestion is one of the problems that is often experienced or encountered, congestion occurs due to the large number of vehicles that exceed the capacity of the road so that it affects road performance. Based on the network pattern seen during holidays or weekends, access to and from the Malang City area tends to increase. Road side barriers that occur on Commander Sudirman street, Singosari are one of the causes of traffic jams. This research aims to provide an alternative plan in overcoming the problem of traffic jams on Commander Sudirman street, Singosari. The method used in this research was based on the 1997 Indonesian Highway Capacity Manual (MKJI), as well as data collection using direct observation methods in the field and then followed by collecting primary data and secondary data. From the research results, the vehicle volume of 2320.6 pcu/hour and degree of saturation (DS) of 0.80 with a level of service (LOS) class D. So it is necessary to divert the route for heavy vehicles (HV) that pass through Commander Sudirman street in the direction of Malang - Surabaya to be diverted via Tumapel street, Ronggowuni street and Kertanegara street, then return to street main route, while for vehicles from Surabaya to Malang that will cross Commander Sudirman street with heavy vehicle types (HV) will follow the current road diversion, namely crossing Rogonoto street, Kebon Agung street, Watu Gede street, and Stasiun street then returning. to the main road as well as installing signs prohibiting parking in the Singosari market shopping area which is on Commander Sudirman street. From the results of this treatment the DS value became 0.76.